1986
DOI: 10.1128/iai.53.3.595-599.1986
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of purified lipoteichoic acid with the classical complement pathway

Abstract: Glycerophosphate-containing lipoteichoic acids (LTAs) interact with the first component of the classical complement pathway (C1). This resulted in the activation of the classical complement pathway in serum, shown by the consumption of Cl, C2, and C4. The dose-dependent interaction of LTAs with purified Cl and Clq was dependent on the negative charges of the phosphate groups of LTA. It was reduced by charge compensation through D-alanine ester substituents and by sterical hindrance through di-and trihexosyl re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 40 publications
(53 reference statements)
2
18
0
Order By: Relevance
“…The resuits reported here showed that LTA from S. mutans caused a dose-dependent conversion of C3 when tested in solution (Figs. 1, 2), The finding complies with results from other studies, based on hemolytic assays (Fiedel & Jackson 1978, Wilkinson et al, 198i, Hummell et al 1985, Loos et al 1986). Degradation of C3 yields split products with important inflammatory potential.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The resuits reported here showed that LTA from S. mutans caused a dose-dependent conversion of C3 when tested in solution (Figs. 1, 2), The finding complies with results from other studies, based on hemolytic assays (Fiedel & Jackson 1978, Wilkinson et al, 198i, Hummell et al 1985, Loos et al 1986). Degradation of C3 yields split products with important inflammatory potential.…”
Section: Discussionsupporting
confidence: 89%
“…First, CI can be activated by certain polyanions in a way simiiar to the effect of immune complexes (Loos & Bitter-Suermann 1976). Thus Loos et al (1986) showed that some forms of LTAs interacted directly with Clq, and triggered a significant consumption of classical pathway proteins. The degree of complement consumption was dependent upon the carbohydrate content of the hydrophihc backbone chain of the LTAs and on their miceliar organization, LTAs with negative charges masked by bulky carbohydrate groups were comparatively weak activators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the latter is true, it would be interesting to study the effect of InlB-LTA complexes on cells. LTA are known to be able to insert into eukaryotic membranes by their lipid moiety and to bind several components, such as the C1q, the type 1 scavenger receptor and fibronectin (Courtney et al, 1983;Loos et al, 1986;Dunne et al, 1994;Hauf et al, 1997). Therefore, how the loose attachment of InlB plays a role in the infectious process of L. monocytogenes remains a challenging issue.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, C1q can bind directly to the bacterial surface to activate the CP. C1q was found to bind to a variety of microbial structures including the lipid A region of LPS (Cooper & Morrison, 1978;Tan et al, 2011) and different outer membrane proteins on Gram-negative bacteria (Loos & Clas, 1987;Albert ı et al, 1993;Mintz et al, 1995;Merino et al, 1998), and LTA on Gram-positive bacteria (Loos et al, 1986). Moreover, C1q can bind to various carbohydrates (Pa€ ıdassi et al, 2008), which potentially mediates direct binding to bacteria.…”
Section: (A) (B)mentioning
confidence: 99%